Youtube to Promote Critical Thinking in Critical Listening Course - Ratri Harida (Journal of English Language Learning, 2023)
When it comes to teaching students listening skills, audio-visual learning techniques are superior to audio-only ones. Therefore, YouTube becomes the primary source to get diverse and high quality videos for critical listening courses. In order to better understand the language, students would be able to connect words and images. Using interviews and observation to collect the data, this research found that using YouTube videos has a positive impact on promoting critical thinking while engaging in a critical listening course. Through 1) freeze framing and prediction; 2) repetition and role play; and 3) reproduction activities, YouTube can help students in a critical listening course develop their critical thinking skills. Further advice on how to maximize the advantages of this activity for promoting critical thinking can be found by looking into the various strategies and techniques used by educators to incorporate YouTube videos into their teaching methods.